Biological education in Belarusian State University for 100 years - Demidchik, Vadim V.; Tikhomirov, Valery N.; Matskevich, Vera S.; Sakhvon, Vitaly V.; Ditchenko, Tatyana I.; Popinachenko, Irina M.; Buga, Sergey V.; Grichik, Vasily V.; Evtushenkov, Anatoly N.; Prokulevich, Vladimir A.; Semak, Igor V.; Smolich, Igor I.; et al. (Experimental Biology and Biotechnology, 2021)
The article is dedicated to the centenary of Belarusian State University and the centenary of biological university education in Belarus. The history of the faculty of biology is described, a retrospective of the development of its units since 1921 is presented. The most significant personalities and events are highlighted. The inseparable connection between the life of the faculty and the university as a whole is demonstrated.
Keywords: faculty of biology; Belarusian State University; history; educational process; scientific research